2, 6‐Dimethoxy‐1, 4‐Benzoquinone Enhances Resistance Against the Rice Blast Fungus Magnaporthe oryzae. Issue 11 (1st April 2014) - Ueno, Makoto; Yoshikiyo, Keisuke
Abstract We investigated the effect of 2, 6‐dimethoxy‐1, 4‐benzoquinone (DMBQ) on induced resistance to Magnaporthe oryzae in rice. DMBQ concentrations greater than 50 μg/ml inhibited spore germination and appressorium formation in M. oryzae. When rice leaves pretreated with 10 μg/ml DMBQ, which did not show antifungal activity against spore germination and appressorium formation of M. oryzae, were inoculated with M. oryzae spores 5 days after DMBQ pretreatment, blast lesion formation was inhibited compared with control leaves pretreated with distilled water. In addition, infection‐inhibiting activity against M. oryzae was significantly enhanced in rice leaf sheaths pretreated with 10 μg/ml DMBQ. H2O2 generation was observed in rice leaves pretreated with DMBQ, and PAL, POX, CHS and PR10a were significantly expressed in these leaves. These results suggested that DMBQ can protect rice from blast disease caused by M. oryzae.